IMPACT OF THE GOOGLE WORKSPACE-BASED INFORMATION SYSTEM FRAMEWORK ON WAREHOUSE MANAGEMENT EFFICIENCY AT PT ROCHE INDONESIA - Arzan Muharom; Maniah Maniah (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2025)
The management of non-standard assets, such as used instruments requiring 'refurbish' or 'destroy' evaluation, presents significant complexity for modern warehouse operations, often lacking the integrated, real-time monitoring systems necessary for timely strategic decision-making. This study addresses this problem by developing and evaluating an agile, cost-effective Warehouse Management System (WMS) framework based on the Google Workspace ecosystem (Google Sheets, Apps Script, Looker Studio). The primary objective is to evaluate the system's effectiveness and to describe the influence of key Information System quality factors—Data Transparency, System Integration, and Real-time Monitoring on Warehouse Performance in a real-world case. This research employed a descriptive case study approach with a total sampling technique involving 100% of the warehouse unit personnel (N=3) at PT Roche Indonesia, alongside an analysis of historical records (110 records from 2023–2024). The study utilizes a comparative analysis between the legacy spreadsheet method and the proposed automated framework. The system's low-code integration, powered by Google Apps Script, proved highly functional in ensuring data consistency. Quantitative results from the user perception survey revealed a high level of satisfaction with an overall average score of 4.82 out of 5.00. Specifically, the system achieved perfect scores in Warehouse Performance (Mean=5.00), followed by strong results in Data Transparency (Mean=4.89) and System Integration (Mean=4.89), while Real-time Monitoring scored 4.67. Furthermore, the implementation successfully eliminated data redundancy (0% duplication rate) compared to the manual legacy system. These findings confirm that the low-code framework significantly enhances operational efficiency and strategic decision-making. This research contributes to the literature by demonstrating the viability and high impact of a low-cost, low-code WMS framework for complex reverse logistics environments.